Charlando : a conversational approach to beginning Spanish - Inman, Sys Strandnes (New York : Holt, Rinehart and Winston, Inc., 1988)
Charlando reduces the grammatical syllabus to a practical and achievable level.
Includes index.
Keywords: SPANISH LANGUAGE -- CONVERSATION AND PHRASE BOOKS -- ENGLISH